Analysis of Success Factors in the Implementation of Regional Government Information System in Palu - Kartika, Aura Dwi; Furqan, Andi Chairil; Zahra, Femilia; Masruddin (Balance : Jurnal Akuntansi dan Manajemen, 2025)
This study aims to identify and analyze the key factors influencing the implementation of the Regional Government Information System (SIPD RI), in order to provide recommendations for more effective and sustainable implementation. The research is grounded in the DeLone and McLean Information System Success Model (2003) and George Edward III’s Policy Implementation Model (1980), employing Principal Component Analysis (PCA) and factor analysis methods. The study adopts an exploratory design with a quantitative approach. Data were collected through questionnaires distributed to 230 SIPD RI users across 41 regional work units (OPD) within the Palu City Government, using a proportionate stratified random sampling technique. The results of the factor analysis, conducted on 37 variable indicators, reveal the emergence of 10 new composite variables representing critical factors in the successful implementation of SIPD RI in Palu City. These factors are labeled as: information quality, organizational support, system benefits, system performance, employee attitudes, technical support, user satisfaction, infrastructure availability, integration and procedures, and system usage. This study offers important implications by contributing to a deeper understanding of the key elements supporting successful SIPD RI implementation. The findings can serve as a guideline for local governments in prioritizing and preparing the identified components, thereby enabling more strategic and effective implementation planning. However, this research is limited in its geographic scope, as it focuses solely on a single region, which may limit the generalizability of the findings to other contexts. Additionally, the limited number and diversity of variables may have resulted in the omission of other potentially significant factors.